2021
DOI: 10.3390/medicines8120077
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Cervical Spine: Frequency of Abnormal Findings with Relation to Age

Abstract: Background: Patients with neck pain are frequently encountered in cervical spine (C-spine) magnetic resonance imaging (MRI) practice. However, the exact distribution and prevalence of cervical abnormalities are not known. Aim: The aim of this study is to evaluate the association between age, gender, and prevalence of abnormal cervical MRI findings. Methods: Records of 111 cervical MRIs were collected in 12 months from January to December 2019 from adults aged 20–89 years who were referred from neurosurgery, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…The conflicting, transient, and limited effect of conservative therapies for CSR management reported in some trials is likely multi-factorial and may be attributed to the unique variables of the individual patient. For example, sustained postural imbalance, represented by cervical hypolordosis or kyphosis, causes increased and altered mechanical loading [ 4 , 5 , 6 , 7 , 8 , 20 , 21 , 22 ]. Once abnormal sagittal cervical alignment becomes established and maintained beyond a critical threshold, the result will be an increase in the probability of pathologies in both the soft and hard tissues of the spine [ 4 , 5 , 6 , 7 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The conflicting, transient, and limited effect of conservative therapies for CSR management reported in some trials is likely multi-factorial and may be attributed to the unique variables of the individual patient. For example, sustained postural imbalance, represented by cervical hypolordosis or kyphosis, causes increased and altered mechanical loading [ 4 , 5 , 6 , 7 , 8 , 20 , 21 , 22 ]. Once abnormal sagittal cervical alignment becomes established and maintained beyond a critical threshold, the result will be an increase in the probability of pathologies in both the soft and hard tissues of the spine [ 4 , 5 , 6 , 7 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, sustained postural imbalance, represented by cervical hypolordosis or kyphosis, causes increased and altered mechanical loading [ 4 , 5 , 6 , 7 , 8 , 20 , 21 , 22 ]. Once abnormal sagittal cervical alignment becomes established and maintained beyond a critical threshold, the result will be an increase in the probability of pathologies in both the soft and hard tissues of the spine [ 4 , 5 , 6 , 7 , 20 , 21 , 22 ]. To this point, in both our study and control groups, we identified a statistically significant negative correlation between cervical lordosis and neck pain for the pre-treatment data (r = −0.49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,26 T2 weighted MRI of a normal cervical spine adapted by Robert Trager to include the trigeminal tract, dotted line, and labels, from Alghamdi et al27 CC-BY-4.0 License. contribute…”
mentioning
confidence: 99%